2023
DOI: 10.1051/0004-6361/202245143
|View full text |Cite
|
Sign up to set email alerts
|

The β Pictoris system: Setting constraints on the planet and the disk structures at mid-IR wavelengths with NEAR

Abstract: Context. β Pictoris is a young nearby system hosting a well-resolved edge-on debris disk, along with at least two exoplanets. It offers key opportunities for carrying out detailed studies of the evolution of young planetary systems and their shaping soon after the end of the planetary formation phase. Aims. We analyzed high-contrast coronagraphic images of this system, obtained in the mid-infrared, taking advantage of the NEAR experiment using the VLT/VISIR instrument, which provides access to adaptive optics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
3
5
1
Order By: Relevance
“…The cat's tail has not been reported before, despite deep HST observations with several instruments (see, e.g., Burrows et al 1995;Golimowski et al 2006;Apai et al 2015;Ballering et al 2016). There is also no evidence for such structure in ALMA data (Dent et al 2014;Matrà et al 2019), nor any of the ground-based mid-infrared observations (e.g., Telesco et al 2005;Li et al 2012;Skaf et al 2023). There may be faint hints of material near this location in the outermost part of the ¢ L -band imaging presented in Milli et al (2014), but only at the edge of the field of view where PSF subtraction residuals make any potential detection highly uncertain.…”
Section: The Cat's Tail In β Picmentioning
confidence: 85%
See 4 more Smart Citations
“…The cat's tail has not been reported before, despite deep HST observations with several instruments (see, e.g., Burrows et al 1995;Golimowski et al 2006;Apai et al 2015;Ballering et al 2016). There is also no evidence for such structure in ALMA data (Dent et al 2014;Matrà et al 2019), nor any of the ground-based mid-infrared observations (e.g., Telesco et al 2005;Li et al 2012;Skaf et al 2023). There may be faint hints of material near this location in the outermost part of the ¢ L -band imaging presented in Milli et al (2014), but only at the edge of the field of view where PSF subtraction residuals make any potential detection highly uncertain.…”
Section: The Cat's Tail In β Picmentioning
confidence: 85%
“…The MIRI data are consistent with that, supporting the inference that the apparent major axis PA does vary with wavelength. At least a partial explanation to this can be found in Skaf et al (2023), where they show in their Figure 6 how the best PA varies for the two different sides of the disk. Besides the IR, the gaseous CO disk in Dent et al (2014) was also inclined ∼4°with respect to the dusty disk, observed in the continuum.…”
Section: Pa Of the Main Diskmentioning
confidence: 99%
See 3 more Smart Citations